Effect of Basic ICT Infrastructure Development on the E-Readiness Ranking of Southeast, Nigeria - Martin Onwudinjo Ugada (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
The study focused on determining the influence of basic ICT infrastructure development on the e-readiness ranking of South East, Nigeria. To carry out this research, a population of 2004 covering two states in South East, Nigeria was chosen. A sample size of 1908 was determined by use of Taro Yamane statistical formula. The descriptive survey research design was employed. Data was generated by use of both primary and secondary sources. These data were analyzed by means of simple percentages, and mean scores, while test of hypothesis was done using the z-test.  Frequencies were applied in data presentation. The study found that provision of basic infrastructural facilities such as functional websites, effective database, laptops / computers for public officials, intra-departmental and inter-ministerial ICT interconnectivity within the MDAs., and 24 –hour online daily services to the citizens, stakeholders and public officials, will ensure a fully networked presence. This is the recommendation of the study, so that the governments of South East, Nigeria can achieve the status of comparative competiveness in the world order of e-readiness